2007
DOI: 10.1029/2006sw000268
|View full text |Cite
|
Sign up to set email alerts
|

Up to 1‐hour forecasting of radiation hazards from solar energetic ion events with relativistic electrons

Abstract: The sudden and prompt occurrence of solar energetic particle events poses a hazard to manned space activities and interferes with robotic space science missions. This study demonstrates the possibility of short‐term forecasting of the appearance and intensity of solar ion events by means of relativistic, near–light speed electrons. A list of the most severe proton events measured by GOES 8 in the years 1996–2002 serves as a basis to derive the fundamentals of the forecasting method with statistical and superpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
183
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(186 citation statements)
references
References 51 publications
2
183
0
1
Order By: Relevance
“…The interplanetary magnetic field sector structure affecting the onset of a few hundreds of keV electrons could reduce the accuracy of proton onset forecast. According to the Posner work (see figure 2 in [7]), this occurred in one case out of a sample of 65 well connected events.…”
Section: Related Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…The interplanetary magnetic field sector structure affecting the onset of a few hundreds of keV electrons could reduce the accuracy of proton onset forecast. According to the Posner work (see figure 2 in [7]), this occurred in one case out of a sample of 65 well connected events.…”
Section: Related Contentmentioning
confidence: 99%
“…Optimization of test-mass discharging can be considered accordingly [6]. Work by Posner [7] has shown that during strong SEP events, relativistic electrons always reach 1 AU in advance of non-relativistic ions. It was found that the intensity increase of both electron and ion fluxes is similar and depends mainly on the magnetic longitude distance (magnetic connection) between spacecraft and flare.…”
Section: Related Contentmentioning
confidence: 99%
“…The Relativistic Electron Alert System for Exploration (REleASE) forecasting scheme uses this effect to predict the proton flux by utilizing the actual electron flux and the increase of the electron flux in the last 60 min. A detailed description of the REleASE scheme can be found in (Posner 2007). The original REleASE code uses real-time electron flux measurements from the Electron Proton Helium Instrument (EPHIN) (Müller-Mellin 1995) on board the Solar and Heliospheric Observatory (SOHO) to forecast the expected proton flux.…”
Section: Predicting 30-50 Mev Sep Events By Using the Release Schemementioning
confidence: 99%
“…In this chapter the two novel real-time SEP forecasting tools developed and operating within the HESPERIA project are presented, based on the University of MAlaga Solar particle Event Predictor (UMASEP) (Núñez 2011(Núñez , 2015 and Relativistic Electron Alert System for Exploration (REleASE) schemes (Posner 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Earth-Moon-Mars Radiation Environment Module (EMMREM) (Schwadron 2010), Predictions of radiation from REleASE, EMMREM and Data Incorporating CRaTER, COSTEP and other SEP measurements (PREDICCS) (Schwadron 2012), Solar Energetic Particle MODel (SEPMOD) (Luhmann et al 2010), SOLar Particle ENgineering Code (SOLPENCO) (Aran et al 2006), and SOLPENCO2 (provides SEP modelling away from 1 AU to the SEP statistical model of the SEPEM project (Crosby et al 2015))) (b) Empirical models (e.g. University of Malaga Solar Energetic Particle (UMASEP) system (Núñez 2011), Relativistic Electron Alert System for Exploration (REleASE) (Posner 2007), Proton Prediction System (PPS) , PROTONS system (Balch 2008), GLE Alert Plus (Kuwabara et al 2006;Souvatzoglou et al 2014) and Laurenza's approach (Laurenza et al 2009)) In some cases forecasting systems rely on methods from both categories such as the SEPForecast tool built under the EU FP7 COMESEP project (263252) (Crosby et al 2012), (http://www.comesep.eu/alert/).…”
Section: Mitigation Proceduresmentioning
confidence: 99%